Middle East respiratory syndrome coronavirus (MERS-CoV) seropositive camel handlers in Kenya - Kiyong'a, A.N.; Cook, Elizabeth A.J.; Okba, N.M.A.; Kivali, V.; Reuksen, C.; Haagmans, B.L.; Fèvre, Eric M. (MDPI, 2020)
Middle East respiratory syndrome (MERS) is a respiratory disease caused by a zoonotic coronavirus (MERS-CoV). Camel handlers, including slaughterhouse workers and herders, are at risk of acquiring MERS-CoV infections. However, there is limited evidence of infections among camel handlers in Africa. The purpose of this study was to determine the presence of antibodies to MERS-CoV in high-risk groups in Kenya. Sera collected from 93 camel handlers, 58 slaughterhouse workers and 35 camel herders, were screened for MERS-CoV antibodies using ELISA and PRNT. We found four seropositive slaughterhouse workers by PRNT. Risk factors amongst the slaughterhouse workers included being the slaughterman (the person who cuts the throat of the camel) and drinking camel blood. Further research is required to understand the epidemiology of MERS-CoV in Africa in relation to occupational risk, with a need for additional studies on the transmission of MERS-CoV from dromedary camels to humans, seroprevalence and associated risk factors.